Forage mission for alleviating feed deficit situation of livestock in Nepal - Sharma, Banshi (Journal of Agriculture and Environment, 2018)
Nepal is divided in five agro-ecological zones. There is feed deficit in every zones except in high mountain regions. There is 34% deficit in animal feed (Singh, 2002). The forage mission* is carried out in 49 districts of the country with the aim of providing sufficient green and dry matter to improved livestock of the country to yield more milk from cattle and buffalo. Similarly more meat from buffaloes, sheep and goats has been obtained. Pasture land improvement is in high mountain areas. In mid hills, cultivation of forages such as stylo, molasses, mulato, setaria, joint vetch, leucaena, napier , forage peanut, desmodium and climbing legumes such as fodder peas have been promoted. In Terai, intensive cultivation of fodder crops: basically winter forages- oat, berseem and vetch is going to be popular. Feeding the legumes and non-legumes forage plant in suitable ratio helps a great extend in livestock production.